2016
DOI: 10.1002/ejhf.711
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of the development of heart failure with preserved ejection fraction by the phosphodiesterase‐5A inhibitor vardenafil in rats with type 2 diabetes

Abstract: AimsHeart failure with preserved ejection fraction (HFpEF) has a great epidemiological burden. The pathophysiological role of cyclic guanosine monophosphate (cGMP) signalling has been intensively investigated in HFpEF. Elevated levels of cGMP have been shown to exert cardioprotective effects in various cardiovascular diseases, including diabetic cardiomyopathy. We investigated the effect of long‐term preventive application of the phosphodiesterase‐5A (PDE5A) inhibitor vardenafil in diabetic cardiomyopathy‐asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 31 publications
3
61
0
Order By: Relevance
“…Interventional Medicine & Applied Science pathways of sildenafil and related drugs, such as detected in experimental animals, appear to actually be compatible with the hypothesis of a favorable effect by PDE5i on hemodynamic parameters and clinical outcomes of patients with HFpEF [21]. Conversely, with regard to the relatively low efficacy of PDE5i on hemodynamic and spiroergometric parameters, as well as on clinical outcomes in patients with HFpEF, as evidenced by some studies included in our metaanalysis [14,19], this might depend on a possible predominance of the cases of Ipc-PH in these studies.…”
Section: Pde5 Inhibitors For Chf Treatmentsupporting
confidence: 54%
“…Interventional Medicine & Applied Science pathways of sildenafil and related drugs, such as detected in experimental animals, appear to actually be compatible with the hypothesis of a favorable effect by PDE5i on hemodynamic parameters and clinical outcomes of patients with HFpEF [21]. Conversely, with regard to the relatively low efficacy of PDE5i on hemodynamic and spiroergometric parameters, as well as on clinical outcomes in patients with HFpEF, as evidenced by some studies included in our metaanalysis [14,19], this might depend on a possible predominance of the cases of Ipc-PH in these studies.…”
Section: Pde5 Inhibitors For Chf Treatmentsupporting
confidence: 54%
“…Also, the loss of insulin sensitivity prevents the utilization of glucose for energy in the cells, thus the body burns fat and muscle as an alternative energy source [46]. Other studies have reported severe weight loss in diabetes mellitus [47,48]. An increase in relative organ weight is indicative of hypertrophy [49].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased activity of this enzyme, which is involved in the reaction of hypoxanthine and xanthine to UA, causes the release of free radicals and increased oxidative stress. Oxidative stress also contributes to the pathogenesis of HFpEF . Several studies have previously examined whether UA‐lowering therapy with xanthine oxidase inhibitor allopurinol or oxypurinol leads to clinical and functional improvement of HF; however, the results are not consistent .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress also contributes to the pathogenesis of HFpEF. 24,25 Several studies have previously examined whether UA-lowering therapy with xanthine oxidase inhibitor allopurinol or oxypurinol leads to clinical and functional improvement of HF; however, the results are not consistent. [26][27][28][29][30] Cingolani and colleagues 26 indicated that inhibition of xanthine oxidase by oxypurinol in patients with chronic HF decreased UA level and improved LVEF in patients with LVEF ≤40% after 1 month of treatment.…”
Section: Discussionmentioning
confidence: 99%